Targeting of dermal myofibroblasts through death receptor 5 arrests fibrosis in mouse models of scleroderma - Jong-Sung Park (Nature Portfolio, 2019)
Dermal myofibroblasts are responsible for fibrosis development in scleroderma. Here the authors show that a bioengineered recombinant human TRAIL ligand reverses established fibrosis in mouse models of scleroderma by targeting the death receptor 5 and inducing apoptosis of myofibroblasts.